Ubiquitous conservative interaction patterns between post-spliced introns and their mRNAs revealed by genome-wide interspecies comparison - Bo, Suling; Sun, Qiuying; Li, Zhongxian; Aodun, Gerile; Ji, Yucheng; Wei, Lihua; Wang, Chao; Lu, Zhanyuan; Zhang, Qiang; Zhao, Xiaoqing (Frontiers in Genetics, 2023)
Introns, as important vectors of biological functions, can influence many stages of mRNA metabolism. However, in the current works, post-spliced introns are not nearly considered. In this study, the optimal matched regions between introns and their mRNAs in 9 model organism genomes are investigated with improved Smith-Waterman local alignment software. Our results showed that the distributions of mRNA optimal matched frequencies are high consistency or universality. There are optimal matched frequence peaks in UTRs, obvious especially in the 3’-UTR. The matched frequencies are relative low in CDS regions of mRNA. The distributions of the optimal matched frequencies aroud functional sites are also labored.The centers of the GC content distributions for different sequences are different. The matched rate distributions are high consistency, they are located mainly between 60% and 80%. The most probable value of the optimal matched segments is about 20bp for low eukaryotes and 30bp for high eukaryotes respectively. These results show that there are abundant functional units in introns, and these functional units are co-correlation structurally with all kinds of sequences for mRNA. The interaction between post-spliced introns and corresponding mRNAs may play a key role in gene expression.